1993
DOI: 10.1029/93ja00762
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Rayleigh‐Taylor instabilities, atmospheric gravity waves and equatorial spread F

Abstract: Although it is generally accepted that equatorial spread F (ESF) is due to nonlinear evolution of the Rayleigh‐Taylor instability, a number of important properties of the process remain unexplained. In particular, we investigate two as yet unexplained features of ESF: the common dominance of very large scale features (≥20 km) and their large amplitude. Although associated for years with spread F we show here for the first time that atmospheric gravity waves can initiate the Rayleigh‐Taylor instability. In agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 43 publications
1
84
0
Order By: Relevance
“…The resultant instabilities grow via the Rayleigh-Taylor mechanism which creates bubbles (or plumes) of plasma which can attain altitudes as high as 1500 km at the equator within a few hours (e.g. Woodman and La Hoz, 1976;Huang et al, 1993). The bubbles are readily observed in radar plots and appear as towering plumes extending from the lower ionosphere to the top side (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant instabilities grow via the Rayleigh-Taylor mechanism which creates bubbles (or plumes) of plasma which can attain altitudes as high as 1500 km at the equator within a few hours (e.g. Woodman and La Hoz, 1976;Huang et al, 1993). The bubbles are readily observed in radar plots and appear as towering plumes extending from the lower ionosphere to the top side (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These plumes are identified as large-scale depletions or equatorial plasma bubbles (EPB) [Sobral et al, 1980] and are believed to be generated by CII mechanism [Sultan, 1996]. Numerous theoretical and numerical studies have been performed to assess the linear and nonlinear aspects of these complex processes [Ossakow et al, 1979;Zargham and Seyler, 1987;Raghavarao et al, 1992;Huang et al, 1993;Keskinen et al, 1998]. These studies revealed the generation of the EPB initiated by a seed perturbation at the bottomside of the rising F layer.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive observations of equatorial plasma bubbles by radar (e.g. Kelley et al, 1981;Hysell et al, 1990;Kelley and Hysell, 1991;Huang et al, 1993), satellite borne ion drift sensors (e.g. Singh et al, 1997), and optical observations of F region night-glow emissions (e.g.…”
Section: Introductionmentioning
confidence: 99%